1984
DOI: 10.1007/bf01946657
|View full text |Cite
|
Sign up to set email alerts
|

Alteichin: an unusual phytotoxin fromAlternaria eichorniae, a fungal pathogen of water hyacinth

Abstract: The phytopathogenic fungus Alternaria eichorniae attacks water hyacinth, an economically significant aquatic weed. The novel phytotoxin alteichin was isolated from liquid cultures of this fungus and its structure was deduced by X-ray crystallographic analysis. Altheichin is a doubly hydrated form of 4,9-dihydroxy perylene-3, 10-quinone. A single step dehydration of alteichin to anhydroalteichin is catalyzed both by acid and by a crude enzyme preparation from water hyacinth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 10 publications
3
39
0
Order By: Relevance
“…The increase in the severity of disease on plants treated with mycelium-filtrate aliginate formulation of pathogen in this study could be due to the fungus being aided by sodium alginate which applied on the plants immediately before inoculation as well as by the pathotoxins produced by the fungus in the cultural medium. Our data agree with those of Robeson et al (1984), Charudattan, 1986 andShabana et al (1997) who found that the most effective formulation causing disease severity was the mycelium filtrate followed by mycelium alone and the least effective to be the formulation of culture filtrate alone. In this connection, sodium alginate is commonly used in many food products (Connick, 1979) and any residues in plants or water would not be toxic to nontarget organisms.…”
Section: Resultssupporting
confidence: 93%
“…The increase in the severity of disease on plants treated with mycelium-filtrate aliginate formulation of pathogen in this study could be due to the fungus being aided by sodium alginate which applied on the plants immediately before inoculation as well as by the pathotoxins produced by the fungus in the cultural medium. Our data agree with those of Robeson et al (1984), Charudattan, 1986 andShabana et al (1997) who found that the most effective formulation causing disease severity was the mycelium filtrate followed by mycelium alone and the least effective to be the formulation of culture filtrate alone. In this connection, sodium alginate is commonly used in many food products (Connick, 1979) and any residues in plants or water would not be toxic to nontarget organisms.…”
Section: Resultssupporting
confidence: 93%
“…Indeed, numerous phytotoxins derived from DHN have been described (93). One of these, alteichin, is a toxic quinone which is secreted by the fungus Alternaria eichhorniae (68).…”
Section: Melanin Biosynthetic Intermediates As Phytotoxinsmentioning
confidence: 99%
“…Some genes involved in melanin biosynthesis have been cloned and sequenced (Perpetua et al, 1996;Takano et al, 1995;Vidal-Cros et al, 1994). In addition, some phytotoxins were discovered as shunt ReKitaproducts of this type of melanin biosynthesis, such as alteichin of Alternaria eichhorniae Nag Raj et Ponnappa (Robeson et al, 1984). However, genetic analyses have not been fully worked out for these fungi.…”
mentioning
confidence: 99%